'Side effects' are 'central effects' that challenge retention in HIV treatment programmes in six sub-Saharan African countries: a multicountry qualitative study. (23rd July 2017) - Renju, Jenny; Moshabela, Mosa; McLean, Estelle; Ddaaki, William; Skovdal, Morten; Odongo, Fred; Bukenya, Dominic; Wamoyi, Joyce; Bonnington, Oliver; Seeley, Janet; Zaba, Basia; Wringe, Alison
Abstract : Objectives: To explore the bodily and relational experience of taking antiretroviral therapy (ART) and the subsequent effect on retention in HIV care in six sub-Saharan African countries. Methods: In-depth interviews were conducted with 130 people living with HIV (PLHIV) who had initiated ART, 38 PLHIV who were lost to follow-up and 53 healthcare workers (HCWs) in Kenya, Uganda, Tanzania, Malawi, Zimbabwe and South Africa. PLHIV were purposely selected to include a range of HIV treatment histories. Deductive and inductive analysis was guided by aspects of practice theory; retention in HIV care following ART initiation was the practice of interest. Results: PLHIV who were engaged in HIV care took ART every day, attended clinic appointments and ate as well as possible. For PLHIV, biomedical markers acted as reassurance for their positive treatment progression. However, many described ART side effects ranging from dizziness to conditions severe enough to prevent them from leaving home or caring for themselves or others. In all settings, the primary concern of HCW was ensuring patients achieved viral suppression, with management of side effects seen as a lower priority. Where PLHIV tolerated side effects, they were deemed the lesser of two evils compared with their pre-ART illnesses. Participants who reported feeling well prior to starting ART were often less able to tolerate side effects, and in many cases these events triggered their disengagement from HIV care. Conclusions: Retention in ART care is rarely an outcome of rational decision-making, but the consequence of bodily and relational experiences. Initiatives to improve retention should consider how bodily experiences of PLHIV relate to the rest of their lives and how this can be respected and supported by service providers to subsequently improve retention in care.